A Case Example of District-Wide Adoption of the Tier 2 Identification and Intervention Framework. Issue 3 (3rd July 2019) - McDaniel, Sara C.; Bruhn, Allison L.
Abstract: The multitiered framework for preventing and addressing discipline and school climate, school-wide positive behavioral interventions and supports, is widely adopted across the United States with much of the focus on Tier 1, universal prevention supports. The following case example describes district-wide adoption of a systematic framework for Tier 2 identification and intervention in a rural, low-income Southwestern district. Both process and outcome measures are presented with regard to implementation fidelity, social acceptability, and tier movement as a preliminary evaluation of the framework. Implications for future research and practice as well as limitations are discussed.